Importance Assessment of Correlated Predictors in Business Cycles Classification - Daniel Enache; Claus Weihs (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
When trying to interpret estimated parameters the researcher is interested in the (relative) importance of the individual predictors. However, if the predictors are highly correlated, the interpretation of coefficients, e.g. as economic ?multipliers?, is not applicable in standard regression or classification models. The goal of this paper is to develop a procedure to obtain such measures of importance for classification methods and to apply them to models for the classification of german business cycle phases.
Keywords: 519; Konjunkturprognose; Prognoseverfahren; Korrelation; Klassifikation; Theorie